The Influence Of Work Environment And Work Stress On Employee Performance (Survey on Production Employees at PT. PERNAS Kabupaten Tasikmalaya) - Febri Dwicky Maulana; Suci Putri Lestari; Dudu Risana (Penerbit Jurnal Indonesia, 2023)
This purpose of this study to determine the influence of work environment and work stress on employee performance (Survey on production employees at PT. PERNAS Kabupaten Tasikmalaya). The method used is a quantitative method with a research sample of 100 respondents who are a production employees. The data is used primary data and secondary data. The analitytical tool in this research is multiple regression using by SPSS version 25. The result showed that simultaneously work environment and work stress has a significant influence on employee performance. Partially work environment has positive and significant influence on employee performance. Partially work stress has positive and significant on employee performance.